2009
DOI: 10.1002/jrs.2185
|View full text |Cite
|
Sign up to set email alerts
|

In situ monitoring of solid‐state transition of p‐aminobenzoic acid polymorphs using Raman spectroscopy

Abstract: The purpose of this study is to investigate the mechanism of solid-state polymorphic transition of p-aminobenzoic acid (PABA) using in situ Raman spectroscopy measurement. The polymorphic transition experiments were conducted on a micro quartz vessel mounted on a microscope, hot and cold stage, under isothermal conditions. The temperature was precisely controlled by a standalone temperature controller equipped with liquid nitrogen cooling system. The Raman spectroscopy probe was positioned on the surface of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Raman bands at 1181.0 and 1133.0 cm −1 found in the chlordiazepoxide physical mixture spectrum disappeared in the co-crystal spectra, while another at 1515.9 cm −1 is shifted to 1521 cm −1 . Moreover, the band at 1287cm −1 in the mixture spectrum assigned to the hydroxyl stretching of p -aminobenzoic acid [ 46 ] changes position slightly to ~1284 cm −1 and a new strong band at 1255 cm −1 , near the hydroxyl band, is created in the co-crystal spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Raman bands at 1181.0 and 1133.0 cm −1 found in the chlordiazepoxide physical mixture spectrum disappeared in the co-crystal spectra, while another at 1515.9 cm −1 is shifted to 1521 cm −1 . Moreover, the band at 1287cm −1 in the mixture spectrum assigned to the hydroxyl stretching of p -aminobenzoic acid [ 46 ] changes position slightly to ~1284 cm −1 and a new strong band at 1255 cm −1 , near the hydroxyl band, is created in the co-crystal spectra.…”
Section: Resultsmentioning
confidence: 99%
“…In 2008 Yang et al 58 confirmed this result and used Raman spectroscopy to measure the rate of the solid state transformation from β to α at temperatures between 78 and 100°C. They observed no intermediate forms and estimated the activation energy to be 136 kJmol -1 .…”
Section: Thermal Analysis and Forms Conversions In Their 2004 Paper mentioning
confidence: 92%
“…Yang et al [243] investigated the mechanism of solid-state polymorphic transition of p-aminobenzoic acid (PABA) using in situ Raman spectroscopy. High-resolution micro-Brillouin scattering and heat capacity studies of polar bis(guanidinium)zirconium bis(nitrilotriacetate) hydrate were performed by Maczka et al [244] in the temperature range 230-305 K.…”
Section: Phase Transitionsmentioning
confidence: 99%
“…Phase transitions were described by Vikram et al 242 involving the dynamics and mechanism of the crystal II smectic G phase transition for erepthal‐bis‐heptylaniline by a temperature‐dependent micro‐Raman study and DFT calculations. Yang et al 243 investigated the mechanism of solid‐state polymorphic transition of p ‐aminobenzoic acid (PABA) using in situ Raman spectroscopy. High‐resolution micro‐Brillouin scattering and heat capacity studies of polar bis(guanidinium)zirconium bis(nitrilotriacetate) hydrate were performed by Maczka et al 244 in the temperature range 230–305 K.…”
Section: Solid‐state Studiesmentioning
confidence: 99%